PENGARUH AUDIT TENURE TERHADAP KUALITAS AUDIT - Aulia Dewi Gizta; Nurfitri Zulaika (Juremi: Jurnal Riset Ekonomi, 2023)
The purpose of this study was to examine the effect of Audit Tenure on audit quality. The population of this research is all auditors at Public Accounting Firms in the Riau Islands Province. The sample in this study used a saturated sampling technique, which allows researchers to collect data from the entire auditor population. The samples in this study were all auditors, partners, senior auditors and junior auditors who actively worked at 10 Public Accounting Firms in the Riau Islands Province. The total number of respondents in this study was 52 auditors. The data collection method was carried out using a questionnaire method. The results of this research indicate that Audit Tenure influences audit quality.